Analisis Etika dan Materialisme dalam Iklan Kontemporer sebagai Strategi Branding di Era Digital - Rr. Ajeng Jelita Cahya Lazuardyne; Siti Amilatus Sholikha; Thouresyah Aprillia; Sophia Kumala Dewi; Mutammima Mutammima; Sukron Makmur; Putri Hikmatul Izza (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2025)
This study aims to analyze the interplay between ethical values and materialism in digital advertising and its impact on branding strategies in the digital era. Using a qualitative literature review approach, the study evaluates 25 national and international journals discussing contemporary ethical dilemmas, such as visual manipulation, transparency issues, and consumerist values in advertising. The findings highlight that while materialism can enhance brand imagery, it risks breaching ethical standards without alignment to honesty and social responsibility. The study also underscores the relevance of Islamic ethical values—such as as-sidq and amanah—in building sustainable branding. Ethical awareness in digital advertising is not just normative but a long-term branding strategy